1995
DOI: 10.1002/cne.903560105
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of sGnRH and cGnRH‐II in the brain of goldfish, Carassius auratus

Abstract: The immunocytochemical distribution of salmon gonadotropin-releasing hormone (sGnRH) and chicken GnRH-II (cGnRH-II) neurons in the brain of goldfish was examined using respective antisera. Salmon GnRH-immunoreactive (ir) cell bodies were localized in the area between the olfactory nerve and the olfactory bulb (the terminal nerve ganglion), the ventral telencephalon, the preoptic area, and the hypothalamus. Chicken GnRH-II-ir cell bodies were observed in the same areas as were those of sGnRH, although the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(83 citation statements)
references
References 22 publications
7
75
1
Order By: Relevance
“…But specificity turned out to be a critical problem when it became clear that different forms of GnRH were produced in the brain of a single species (Yu et al 1988). Nevertheless, using wellcharacterized antibodies, several studies succeeded in showing the differential expression pattern of two different GnRHs, for example in the brain of the Masu salmon (Amano et al 1991), the Siberian sturgeon (Leprêtre et al 1993), the European eel (Montero et al 1994) or the goldfish (Kim et al 1995). The cDNA sequences encoding different GnRH forms allowed this problem to be approached by using in situ hybridization.…”
Section: Discussionmentioning
confidence: 99%
“…But specificity turned out to be a critical problem when it became clear that different forms of GnRH were produced in the brain of a single species (Yu et al 1988). Nevertheless, using wellcharacterized antibodies, several studies succeeded in showing the differential expression pattern of two different GnRHs, for example in the brain of the Masu salmon (Amano et al 1991), the Siberian sturgeon (Leprêtre et al 1993), the European eel (Montero et al 1994) or the goldfish (Kim et al 1995). The cDNA sequences encoding different GnRH forms allowed this problem to be approached by using in situ hybridization.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have shown that GnRH neurons and their fibers also exist in various areas of the brain other than the hypothalamus (extrahypothalamic GnRH neurons) (Amano et al 1991;Kim MH et al 1995;Munz et al 1981;Schwanzel-Fukuda and Silverman 1980;Schwanzel-Fukuda et al 1985;Yamamoto et al 1995). Such extrahypothalamic GnRH systems have been identified in the terminal nerve (TN) and midbrain.…”
Section: Introductionmentioning
confidence: 99%
“…The olfactory bulb receives prominent projections of GnRH-containing fibers from the TN (Amano et al 1991;D'Aniello et al 1995;Gonzalez-Martinez et al 2001, 2002Kim KH et al 1999;Kim MH et al 1995;Oka and Ichikawa 1990;Teruyama and Beck 2000;Yamamoto et al 1995) and their GnRH content appears to be affected by the multimodal sensory inputs to the animals (Dluzen and Ramirez 1983; Dluzen et al 1981; Yu and Peter 1990), suggesting that TN regulates the responsiveness of the olfactory bulbar neural circuits in accordance with these sensory inputs. However, it is not yet clear whether the activities of these neural circuits are modulated by GnRH.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to salmonids, goldfish possess both forms of GnRH in the pituitary (Yu et al 1987(Yu et al , 1988Kim et al 1995). Therefore, it is interesting to examine whether both GnRHs have the potency to stimulate FSH and LH secretion in salmonid species.…”
Section: -1 Effects Of Gnrh On Gth Release In Sockeye Salmonmentioning
confidence: 99%